Population Structure Based On Mitochondrial Cytochrome Oxidase Subunit I (Coi) Gene In The Black Scar Oyster, Crassostrea Iredalei (Faustino, 1932) In Malaysia - Abidin, Danial Hariz Zainal (2013)
Mitochondrial cytochrome oxidase subunit I (COI) gene was utilised to assess the population genetics and phylogeographic relationships of the commercially important black scar oyster, C. iredalei among 11 populations throughout Peninsular Malaysia and Sabah. Overall, populations of C. iredalei demonstrated low nucleotide diversity π (0.000 – 0.004) and low-to-high haplotype diversity h (0.000 – 0.795) levels. Genetic structuring was detected between the Peninsular Malaysia and Sabah populations as revealed by the FST and AMOVA analyses. However, the COI gene analyses showed minimal and non-significant (P>0.05) population differentiation within the Peninsular Malaysia and Sabah regions. Relative genetic homogeneity was reported within the coastal populations of Peninsular Malaysia and Sabah, respectively. These could be attributed to both high larval dispersal along the east and west coasts and human-driven spat translocation between the two coastlines due to C. iredalei cultivation practices. The neutrality and mismatch distribution analyses supported the hypothesis that C. iredalei had experienced a/several bottleneck event(s), followed by population expansion. The molecular information obtained from this study can be incorporated in a pragmatic aquaculture management strategy of wild broodstock and the hatchery lines of C. iredalei in Malaysia. A Next Generation Sequencing (NGS) approach, Ion Torrent technology was utilized in the development of novel microsatellite markers in C. iredalei. Although a total number of 2424 microsatellite motif repeats were identified, of which, 137 qualified for primer design in the present study.